Implementation of Lean Manufacturing in Reducing Waste and Improving Efficiency in Tapioca Flour Production - Dhea Oktavia Saputri; Joumil Aidil Saifuddin (Universitas KH. Abdul Chalim Mojokerto, 2026)
PT XYZ manufactures tapioca flour. This company faces various wastes in its production process, including defects, waiting, unnecessary inventory, overprocessing, unnecessary motion, overproduction, and transportation. This study uses a lean manufacturing approach, Value Stream Mapping, to identify and minimize waste, enhancing production time efficiency, and the kaizen method as a proposed improvement. The research was carried out through production flow mapping using Current Value Stream Mapping (CVSM) to pinpoint inefficiencies, Value Stream Analysis Tools (VALSAT) to determine tools, and fishbone diagrams for root cause analysis. Production efficiency is measured by Process Cycle Efficiency (PCE) before and after repairs. Proposed improvements include the implementation of kaizen through PDCA and 5S methods, as well as the preparation of Standard Operating Procedures (SOP) and the use of trolleys to improve the efficiency of product transfer. The results indicated a reduction in production lead time from 1,429 minutes to 1,194 minutes and a PCE increase from 63.89% to 76.47%.